Amine modified hierarchical structure photocatalytic material as well as preparation method and application thereof
By performing ethylenediamine modification and silver loading on TiO2@Na2Ti3O7 composite material, the problem of poor CO2 capture and charge transfer during the CO2 reduction process was solved, and efficient CO2 reduction performance was achieved, and CH4 activity was significantly improved. Have good application prospects.
Patent Information
- Application Number
- CN202411252621.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-09
AI Technical Summary
During the CO2 reduction process, existing photocatalytic materials have problems such as difficulty in coordinating CO2 capture and reduction reactions and poor charge transfer, resulting in low catalytic efficiency.
The multi-structured TiO2@Na2Ti3O7 composite material is used for ethylenediamine modification and silver loading. Through the synergistic effect of silver adsorption activation site and ethylenediamine, CO2 capture is enhanced, and charge separation and migration is promoted through Na+, and Ag acts as an electron trap inhibition. Charge reflux improves electron utilization.
The photocatalytic CO2 reduction efficiency is significantly improved, and the CH4 activity reaches 9.01 μmol/g/h, which significantly improves the CO2 capture and reduction performance and has good application prospects.
Smart Images

Figure CN119237009A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of CO2 reduction photocatalytic materials technology, specifically to an amine-modified hierarchical structure photocatalytic material, its preparation method, and its application. Background Technology
[0002] Converting CO2 into valuable related chemicals can contribute to the carbon circular economy. Photocatalysis technology directly utilizes solar energy, requiring no additional energy consumption. However, CO2 reduction must consider substrate and intermediate adsorption, charge transfer, and other factors. Simultaneously coordinating CO2 capture and reduction reactions with excellent performance is challenging. It is well known that highly efficient photocatalytic reactions possess advantages such as strong light absorption and conversion capabilities, rapid charge separation and migration, and rapid catalytic reaction. Catalysts rich in active sites have strong adsorption and activation capabilities for CO2 molecules. Photogenerated charges migrate rapidly on the catalyst surface, and intermediate products are easily desorbed and transferred during the catalytic process, accelerating surface redox reactions and improving catalytic conversion efficiency.
[0003] Focusing on photocatalytic material systems, high component tunability and easy bulk polarization are required. TiO2 is a research hotspot in the field of photocatalysis due to its high elemental abundance and good chemical stability. Based on the TiO6 octahedron as the basic structural unit, its energy bands are dominated by O 2p and Ti 3d orbitals, whose size and position are controllable. A wide absorption range and high absorption intensity are often difficult to achieve simultaneously; morphology manipulation is a common method to enhance photocatalytic activity. Among various morphologies, alkali metal titanates (M... x TiO y TiO2-M has attracted attention due to its unique layered stepped pore structure and rapid charge separation and migration. It utilizes weak interlayer interactions to achieve bulk phase "surface formation," enabling the uniform distribution of heteroatoms within the material bulk phase and inducing bulk phase polarization. Current research has already yielded results for the preparation of TiO2-M. x TiO y The composite material has been applied to photocatalytic degradation, water splitting and hydrogen evolution, etc. It utilizes the built-in electric field to drive the reverse movement of photogenerated charges to migrate to the material surface and achieve good catalytic effect. However, its application in photocatalytic CO2 reduction is relatively limited.
[0004] Surface modification is one of the effective ways to improve the photocatalytic CO2 reduction performance. Strong CO2 adsorption on the material surface is a prerequisite for high reduction activity; insufficient adsorption strength will terminate the reaction. Common surface modifications include Lewis acids / bases, metals, and metal oxides. However, single modifications often suffer from limited functionality. Constructing synergistic sites can simultaneously achieve efficient CO2 adsorption and activation.
[0005] Based on the above analysis, the following design approach is proposed: synthesize a TiO2@Na2Ti3O7 composite material with multiple structures, while simultaneously modifying the surface with ethylenediamine and loading it with silver. On the one hand, silver acts as an activation site for CO2 and H2O adsorption, and synergistically enhances CO2 capture with ethylenediamine; on the other hand, Na... + Ag promotes charge separation and migration as well as orderly enrichment on the surface. It acts as an electron trap and enhances electron utilization by suppressing charge backflow through the Schottky barrier. Summary of the Invention
[0006] The purpose of this invention is to provide an amine-modified hierarchical photocatalytic material, its preparation method, and its application, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A method for preparing an amine-modified hierarchical photocatalytic material, comprising the following steps:
[0009] S1. Add ethylene glycol to a round-bottom flask, then add tetrabutyl titanate dropwise and sonicate until homogeneous. Reflux in an oil bath at 110-130℃ for 0.8-1.5h. After the reaction is complete, cool completely for later use. Wash with water and ethanol, then dry in a forced-air drying oven at 55-65℃ to obtain a white powder.
[0010] S2. The white powder obtained in step S1 is ultrasonically dispersed in deionized water, and then ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a reaction vessel and reacted at 160-210℃ for 5.4-6.8h. After the reaction is completed, the mixture is cooled to room temperature, washed, and vacuum dried at 45-70℃ for 10-16h to obtain amine-modified protonated titanate (NH2-H2Ti2O5·H2O).
[0011] S3. The protonated titanic acid and sodium hydroxide prepared in step S2 are ultrasonically dissolved in deionized water, ethylene glycol is added, and silver nitrate solution with a concentration of 1 mol / L is added and ultrasonically dissolved until completely dispersed to obtain a mixed solution.
[0012] S4. Add the mixed solution obtained in step S3 to the reaction vessel and react at 150-200℃ for 11-14 hours. After the reaction is complete, wash and dry under vacuum at 50-70℃ overnight to obtain the amine-modified hierarchical photocatalytic material (NH2 / TiO2@Na2Ti3O7-Ag).
[0013] Furthermore, in step S1, the volume ratio of ethylene glycol to tetrabutyl titanate is 40:1.
[0014] Furthermore, the volume ratio of tetrabutyl titanate in step S1 to deionized water and ethylenediamine in step S2 is 2:25:45, and the cleaning step in step S2 includes rinsing three times with deionized water and then rinsing once with anhydrous ethanol.
[0015] Furthermore, in step S3, the mass ratio of protonated titanic acid, sodium hydroxide, and deionized water is 2:1:200, and in step S2, the volume ratio of ethylene glycol, deionized water, and silver nitrate is (1-3):1:(0.0005-0.005).
[0016] Furthermore, the cleaning step in step S4 includes first washing with deionized water to the center, and then washing once with ethanol.
[0017] An amine-modified hierarchical photocatalytic material is prepared using the aforementioned method for preparing amine-modified hierarchical photocatalytic materials.
[0018] A photocatalytic material prepared by a method for preparing an amine-modified hierarchical structure photocatalytic material, or the application of an amine-modified hierarchical structure photocatalytic material in the field of CO2 catalysis.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] This invention successfully synthesized a TiO2@Na2Ti3O7 composite material with multiple structures via a hot solvent method, while simultaneously modifying the surface with ethylenediamine and loading it with silver. On the one hand, silver acts as an activation site for CO2 and H2O adsorption, and synergistically enhances CO2 capture with ethylenediamine; on the other hand, Na... + By promoting charge separation and migration and orderly enrichment on the surface, Ag acts as an electron trap, suppressing charge backflow and improving electron utilization through the Schottky barrier. The synergistic effect between Ag and Ag greatly enhances photocatalytic efficiency, showing excellent application prospects in CO2 capture and reduction. With a silver nitrate dosage of 0.025 ml, the catalytic material was tested for photocatalytic CO2 reduction in pure water, achieving a CH4 activity of 9.01 μmol / g / h. Attached Figure Description
[0021] Figure 1 This is a process flow diagram of the present invention;
[0022] Figure 2 The images shown are SEM and EDX images of the solvothermal products when the EG / H2O ratio is 20 / 20 in step S3 of Example 1 of the present invention.
[0023] Figure 3 The images shown are SEM and EDX images of the solvothermal products when the EG / H2O ratio is 30 / 10 in step S3 of Example 6 of this invention.
[0024] Figure 4 The images shown are SEM and EDX images of the amine-modified hierarchical photocatalytic material in Example 1 of this invention.
[0025] Figure 5 The images are XRD and FT-IR images of Ag, NTN, and NTN-Ag in Examples 1-4 of this invention.
[0026] Figure 6 NTN and NTN-Ag in Embodiment 1 of the present invention 0.025 XPS images, including (a) survey, (b) Ti 2p, (c) O 1s, (d) Na 1s, (e) N 1s and (f) Ag 3d;
[0027] Figure 7 The photocatalytic CO2 reduction activity of the NTN and NTN-Ag composite materials in Examples 1-4 of this invention is shown. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Please see Figures 1 to 7 The present invention provides:
[0030] Example 1
[0031] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0032] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 120°C for 1 hour. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a 60°C forced-air drying oven to obtain a white powder.
[0033] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 180 °C for 6 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 60 °C for 12 h to obtain amine-modified protonated titanate.
[0034] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 20ml of deionized water by ultrasonication, add 20ml of ethylene glycol, and continue to add 0.025ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0035] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 180 °C for 12 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and vacuum dry at 60 °C overnight to obtain the amine-modified hierarchical photocatalytic material (NH2 / TiO2@Na2Ti3O7-Ag), abbreviated as NTN-Ag, for example, NTN-Ag. 0.025 Add 0.025 mL of AgNO3.
[0036] Example 2
[0037] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0038] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 120°C for 1 hour. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a 60°C forced-air drying oven to obtain a white powder.
[0039] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 180 °C for 6 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 60 °C for 12 h to obtain amine-modified protonated titanate.
[0040] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 20ml of deionized water by ultrasonication, add 20ml of ethylene glycol, and continue to add 0.01ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0041] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 180 °C for 12 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and dry under vacuum at 60 °C overnight to obtain NTN-Ag. 0.01 .
[0042] Example 3
[0043] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0044] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 120°C for 1 hour. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a 60°C forced-air drying oven to obtain a white powder.
[0045] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 180 °C for 6 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 60 °C for 12 h to obtain amine-modified protonated titanate.
[0046] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 20ml of deionized water by ultrasonication, add 20ml of ethylene glycol, and continue to add 0.05ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0047] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 180 °C for 12 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and dry under vacuum at 60 °C overnight to obtain NTN-Ag. 0.05 .
[0048] Example 4
[0049] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0050] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 120°C for 1 hour. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a 60°C forced-air drying oven to obtain a white powder.
[0051] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 180 °C for 6 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 60 °C for 12 h to obtain amine-modified protonated titanate.
[0052] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 20ml of deionized water by ultrasonication, add 20ml of ethylene glycol, and continue to add 0.1ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0053] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 180 °C for 12 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and dry under vacuum at 60 °C overnight to obtain NTN-Ag. 0.1 .
[0054] In steps S3 of Examples 1-4, the ratio of ethylene glycol to deionized water is 20:20 (EG / H2O ratio is 20 / 20);
[0055] Example 5
[0056] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0057] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 110 °C for 0.8 h. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a 55 °C forced-air drying oven to obtain a white powder.
[0058] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 160 °C for 5.4 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 45 °C for 10 h to obtain amine-modified protonated titanate.
[0059] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 20ml of deionized water by ultrasonication, add 25ml of ethylene glycol, and continue to add 0.025ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0060] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 150 °C for 11 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and dry under vacuum at 50 °C overnight to obtain NTN-Ag. 0.025 .
[0061] Example 6
[0062] A method for preparing an amine-modified hierarchical photocatalytic material comprises the following steps:
[0063] S1. Add 80 ml of ethylene glycol to a round-bottom flask, then add 2 ml of tetrabutyl titanate and sonicate until homogeneous. Reflux in an oil bath at 130°C for 1.5 h. After the reaction is complete, cool completely for later use. Wash with water and ethanol and dry in a forced-air drying oven at 65°C to obtain a white powder.
[0064] S2. The white powder obtained in step S1 is ultrasonically dispersed in 25 ml of deionized water, and then 45 ml of ethylenediamine is added and ultrasonically homogenized to obtain a reaction solution. The reaction solution is transferred to a 100 ml reaction vessel and reacted at 210 °C for 6.8 h. After the reaction is completed, it is cooled to room temperature, washed three times with deionized water and once with ethanol, and then vacuum dried at 70 °C for 16 h to obtain amine-modified protonated titanate.
[0065] S3. Dissolve 0.2g of protonated titanic acid and 0.1g of sodium hydroxide prepared in step S2 in 10ml of deionized water by ultrasonication, add 30ml of ethylene glycol, and continue to add 0.025ml of silver nitrate solution with a concentration of 1mol / L and ultrasonicate until completely dispersed to obtain a mixed solution.
[0066] S4. Add the mixed solution obtained in step S3 to a 100 ml reaction vessel and react at 200 °C for 14 h. After the reaction is complete, wash with deionized water until neutral, wash once with ethanol, and dry under vacuum at 70 °C overnight to obtain NTN-Ag. 0.025 .
[0067] Sample characterization methods
[0068] X-ray powder diffraction (XRD) was performed using an Ultima IV diffractometer at a scanning range of 20–80°, 40 kV, 40 mA, and 10° / min. Morphology observation and elemental mapping analysis (SEM and EDX) were conducted on a Gemini SEM 300. Elemental composition, binding energy, and valence band were determined using X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha+). The UV-Vis diffuse reflectance spectrum (UV-DRS) of the material was measured using a Shimadzu UV2550 spectrophotometer in the wavelength range of 200–800 nm. The results were analyzed using CHI. The transient photocurrent response (TPC), photocurrent (PC), and electrochemical impedance (EIS) were measured using a 760E electrochemical workstation and a three-electrode system (Pt counter electrode, Hg / Hg2Cl2 or Ag / AgCl reference electrode, and FTO working electrode). The TPC and PC test solutions were 0.2M sodium sulfate solutions, and the EIS test solution was a 5mM mixture of potassium ferrocyanide, potassium ferrocyanide, and potassium chloride. The Fourier transform infrared (FT-IR) spectra of the samples were measured on an infrared spectrometer (Nicolet iS10) to analyze the amino groups on the material surface, with potassium bromide as a dilution.
[0069] Photocatalytic CO2 reduction method
[0070] The reduction test was conducted in a quartz reactor with a volume of approximately 200 mL. 50 mg of sample was dissolved in 1 mL of deionized water, and after complete ultrasonic dispersion, it was uniformly deposited in a glass petri dish with a diameter of 3.5 cm. At the same time, 10 mL of deionized water was added to the bottom of the reactor as a water vapor source. The petri dish was placed at the bottom of the reactor. The photocatalytic CO2 reduction experiment was carried out under simulated sunlight. Before turning on the lamp, high-purity CO2 was bubbled into the bottom of the reactor for 0.5 h to remove dissolved oxygen and air to create a pure CO2 environment. The temperature of the reduction system was maintained at 25 °C by circulating condensate. A 300 W xenon lamp (CEL-HXF300, CEAULIGHT Beijing) was used as the light source. After turning on the lamp, 1 mL of gas was drawn up with a syringe every 1 h and injected into a gas chromatograph (GC-7900, CEAULIGHT Beijing) for analysis using an FID detector.
[0071] Characterization results
[0072] Reference Figure 2 (SEM and EDX images of the samples) Sodium titanate nanosheets were obtained with an EG / H2O ratio of 20 / 20, and further increases in EG content (refer to...) Figure 3 ), giving full play to EG and Na + The chelation and support functions of Na successfully bound Na + Introducing interlayer, and again targeting Na + OH - The interaction of EG and its three components yields a 0D / 1D@2D structure, which can be summarized as follows: Na + Infiltration into the interlayer promotes the interaction and coordination between EG and the Ti-O surface, and OH - It will attack the -NH3 on the surface of the nanosheets + / H + Charge imbalance leads to defects, nanosheet curling, and the chelating effect of EG also causes nanosheet aggregation. When these three interact, OH... - Attack between layers - NH3 + / H + This exposes the inner layer, while EG forms a complex with the material surface and simultaneously stabilizes Na. + This will support the surface nanosheet structure to remain unchanged, forming the Na2Ti3O7 phase.
[0073] SEM and EDX images of the hot solvent product when the EG / H2O ratio is 30 / 10
[0074] Since excessive Na+ can cause severe charge recombination, which is counterproductive, subsequent synthesis studies were conducted with the EG / H2O ratio controlled at 20 / 20. Figure 4 They are NTN-Ag 0.025SEM and EDX images; Under the combined action of EG and NaOH, NH2-H2Ti2O5·H2O, after surface reconstruction, still retains a 0D-1D@2D structure, with an overall rod-like shape and a surface composed of stacked nanosheets. The presence of Na in the EDX confirms the successful synthesis of the sodium titanate phase. Silver reduction and the formation of sodium titanate nanosheets are synchronous. NTN-Ag 0.025 A large number of silver particles can be observed scattered on the surface of the nanosheets in the sample, and the silver nanoparticle signal is very obvious in EDX.
[0075] Figure 5 (a) The XRD pattern of the product collected during silver reduction alone without the addition of protonated titanate, compared with Ag. 0 The XRD patterns matched (JCPDS No. 1-1167), confirming that the EG / H2O system can be used for Ag. 0 The load; Figure 5 (b) is the NTN with an EG / H2O ratio of 20 / 20, which is also matched with brookite TiO2 (JCPDS No. 18-875) and Na2Ti3O7 (JCPDS No. 31-1329), successfully constructing TiO2@Na2Ti3O7 again. The diffraction angles of 37.8° and 43.8° are the (111) and (200) crystal planes of elemental silver; Figure 5 (c) shows that the intensity of the diffraction peak increases with increasing silver loading; Figure 5 (d) represents NTN and NTN-Ag 0.025 The FT-IR spectrum can be seen at 3400 cm⁻¹ -1 1630cm -1 There are two distinct absorption peaks at the point, the former corresponding to the stretching vibration of NH and the latter to the bending vibration of NH, indicating that the surface amine functionalization modification was successfully performed.
[0076] XPS is commonly used to analyze the elemental composition and chemical states of elements on the surface of materials; Figure 6 In (a), NTN-Ag 0.025 It displays signals for five elements: Ti, O, Na, N, and Ag. Figure 6 (b) The binding energies of 458 and 464 eV are attributed to Ti, respectively. 4+ 2p 3 / 2 and Ti 2p 1 / 2 The satellite peak at 460 eV belongs to Ti. 3+ ; Figure 6 (c) The binding energies of approximately 530 and 531 eV correspond to lattice oxygen (Ti-O) and surface hydroxyl groups (OH); Figure 6 (d) The Na 1s singlet is around 1071 eV; Figure 6The XPS spectrum of N1s in (e) shows two peaks at approximately 399 and 400 eV, corresponding to the diffraction peaks of -NH2 and NH, respectively, further demonstrating the successful surface amine functionalization. Figure 6 (f) contains two prominent peaks, namely Ag 3d 5 / 2 (367.5eV) and 3d 3 / 2 (373.5 eV), a difference of 6 eV, indicating that it is elemental silver; compared with NTN, NTN-Ag 0.025 The binding energies of Ti 2p, O 1s, and Na 1s shift towards higher binding energies, indicating that the loaded Ag... 0 The altered electronic environment of the support induces electron transfer and localization onto the Ag by the strong interaction between Ag and the NTN support; at the same time, the increased charge density of ethylenediamine also makes it more favorable for carbon dioxide adsorption.
[0077] The photocatalytic CO2 reduction activity was evaluated in a pure water system using CH4 and CO yields, with four NTN-Ag samples prepared in Examples 1-4 used as evaluation objects. Figure 7 As shown, amine-modified protonated titanate exhibits extremely low activity, with CH4 and CO generation rates of 0.14 and 0.02 μmol / g / h, respectively, and an electron selectivity of approximately 96% for CH4. Surface loading with Ag significantly enhances the activity; among them, NTN-Ag... 0.025 The CH4 activity was 9.01 μmol / g / h, which was nearly 64 times higher than that of the monomer. At the same time, the CO activity was also significantly improved. Further increasing the loading amount resulted in a decrease in activity. Comparing the ratio of CH4 to CO activity, it can be seen that the addition of Ag further improved the CH4 selectivity. Ag and surface amino groups worked together to inhibit the desorption of CO to form CO, and instead continued to convert it to CH4 through hydrogenation.
[0078] This invention utilizes a solvothermal method to achieve surface reconstruction of amine-modified protonated titanate using the combined action of sodium hydroxide and ethylene glycol. This successfully yielded a homogeneous NH₂-TiO₂@Na₂Ti₃O₇ catalytic support (with a brookite core) possessing an 0D / 1D@2D structure, while simultaneously loading Ag nanoparticles. In photocatalytic CO₂ reduction tests, the optimal Ag loading was 0.025 mmol, resulting in a CH₄ activity as high as 9.01 μmol / g / h. Photoelectrochemical testing revealed that the synergistic adsorption of ethylenediamine and silver plays a decisive role in improving CO₂ reduction performance. Although ethylenediamine improves the CO₂ adsorption performance on the material surface, due to the lack of effective charge transfer, most adsorption sites cannot be further activated and reduce CO₂, remaining ineffective active sites with low catalytic efficiency. Silver loading not only improves the photoelectrochemical properties of the material but also co-adsorbs and activates CO₂ with ethylenediamine, promoting its hydrogenation reduction, thus fully utilizing the adsorption performance of ethylenediamine. In this invention, sodium titanate is prepared by using sodium hydroxide and ethylene glycol. At the same time, the photocatalytic efficiency is greatly improved through the synergistic effect of surface amine modification and Ag loading.
[0079] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an amine-modified hierarchical structure photocatalytic material, characterized in that: Prepared by the following method: S1. Add ethylene glycol to a round-bottom flask, then drop butyl titanate and mix evenly with ultrasound, reflux in an oil bath at 110-130°C for 0.8-1.5h, cool completely for standby use after the reaction is completed, wash with water and ethanol, and dry in a 55-65°C forced air drying oven to obtain a white powder; S2, ultrasonically dispersing the white powder obtained in step S1 into deionized water, then adding ethylenediamine and continuing ultrasonication to obtain a reaction solution, transferring the reaction solution to a reactor and reacting at 160-210° C. for 5.4-6.8 hours, cooling to room temperature after the reaction, washing, and vacuum drying at 45-70° C. for 10-16 hours to obtain amine-modified protonated titanic acid; S3, ultrasonically dissolving the protonated titanic acid and sodium hydroxide prepared in step S2 in deionized water, adding ethylene glycol, and continuing to add a silver nitrate solution with a concentration of 1 mol / L and ultrasonically dispersing until completely dispersed to obtain a mixed solution; S4. Add the mixed solution obtained in step S3 into a reactor, react at 150-200° C. for 11-14 hours, and after the reaction is completed, wash and vacuum dry at 50-70° C. overnight to obtain an amine-modified hierarchical structure photocatalytic material.
2. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: In step S1, the volume ratio of ethylene glycol to butyl titanate is 40:
1.
3. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: The volume ratio of butyl titanate in step S1 to deionized water and ethylenediamine in step S2 is 2:25:45, and the cleaning step in step S2 includes first cleaning three times with deionized water and then cleaning once with anhydrous ethanol.
4. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: The mass ratio of protonated titanic acid, sodium hydroxide and deionized water in step S3 is 2:1:200, and the volume ratio of ethylene glycol, deionized water and silver nitrate in step S2 is (1-3):1:(0.0005-0.005).
5. The method for preparing the amine-modified hierarchical structure photocatalytic material according to claim 1, characterized in that: The cleaning step in step S4 includes first washing to the center with deionized water and then washing once with ethanol.
6. An amine-modified hierarchical structure photocatalytic material, characterized in that: The photocatalytic material is prepared by the method for preparing the amine-modified hierarchical structure photocatalytic material as described in any one of claims 1 to 5.
7. Use of the photocatalytic material prepared by the method for preparing the amine-modified hierarchical structure photocatalytic material according to any one of claims 1 to 5 or the amine-modified hierarchical structure photocatalytic material according to claim 6 in the field of catalyzing CO2.
Citation Information
Patent Citations
Preparation method and use of silver-supported titanium dioxide photocatalyst
CN109967074A
Preparation method of anatase type nano titanium dioxide microspheres
CN111994950A
Preparation method of composite photocatalytic material
CN114029043A
